Mechanical performance of 3D printed polyether-ether-ketone nanocomposites: An experimental and analytic approach. (1st February 2023) - Rinaldi, Marianna; Bragaglia, Mario; Nanni, Francesca
Abstract: Polyether-ether-ketone (PEEK) nanocomposites with different amount of CNT (i.e. 3 %, 5 %, 10 % by weight) have been produced in the form of filaments and successively 3D printed via fused filament fabrication. Different analytical models, based on rule of mixture and mechanical percolation have been applied to evaluate the elastic modulus and the ultimate tensile strength of PEEK-CNT composites. From the comparison of the predicted mechanical properties with those obtained experimentally the combination of Takayanagi I and Takayanagi II models, based on mechanical percolation, allows to compute the elastic modulus trend of the composites with an error less than 10 %. The ultimate tensile strength Takayanagi model well represents the behaviour found experimentally, with predicted values being slightly higher than the measured ones (error < 11 %). The analytical models cannot be applied to predict the mechanical behaviour of 3D printed parts because it is shown that mechanical properties of additive manufactured composites are deeply influenced by the sum of mechanical percolative behaviour and the interphase strength among 3D printed layers.